2017
DOI: 10.3389/fpls.2017.01411
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cultivar and Maternal Environment on Seed Quality in Vicia sativa

Abstract: Production of high quality seeds is of fundamental importance for successful crop production. However, knowledge of the effects of increased temperature resulting from global warming on seed quality of alpine species is limited. We investigated the effect of maternal environment on seed quality of three cultivars of the leguminous forage species Vicia sativa, giving particular attention to temperature. Plants of each cultivar were grown at 1700 and 3000 m a.s.l., and mass, germination, electrical conductivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…Seed germination is the beginning of the life history for seed plants ( Donohue et al, 2010 ; Nonogaki et al, 2010 ; Lai et al, 2015 ). It has been suggested that one way in which the environment indirectly affects seed germination is through the types and amounts of compounds transferred from the mother plant to the seeds ( Donohue, 2009 ; Baskin and Baskin, 2014 ; Li et al, 2017 ). This transfer of compounds to seeds includes carbohydrates, proteins and lipids, which are the major reserves in most seeds ( Alencar et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Seed germination is the beginning of the life history for seed plants ( Donohue et al, 2010 ; Nonogaki et al, 2010 ; Lai et al, 2015 ). It has been suggested that one way in which the environment indirectly affects seed germination is through the types and amounts of compounds transferred from the mother plant to the seeds ( Donohue, 2009 ; Baskin and Baskin, 2014 ; Li et al, 2017 ). This transfer of compounds to seeds includes carbohydrates, proteins and lipids, which are the major reserves in most seeds ( Alencar et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The maternal growing environment affects not only plant productivity but also seed quality traits of C 3 and C 4 crops [1,2]. Quality seed production is crucial for the initial establishment of plants in the natural environment, such as prairies, where big bluestem establishes naturally from seeds and spreads through vegetative growth [3].…”
Section: Introductionmentioning
confidence: 99%
“…(Gao et al, 2012), and Ricinus communis L. (Severino and Auld, 2013), suggesting that large seeds with high carbohydrates, proteins, and free AA reserves provide more energy to fuel germination than small seeds. However, V. sativa seeds (Li et al, 2017) produced at increased temperatures had a significantly low seed mass and FGP and long T50 because the high‐temperature stress accelerated seed growth rate and decreased photosynthetic assimilation to synthesize seed storage compounds that negatively affect seed mass, thereby lowering seed germination traits (Hampton et al, 2013). Thus, improved soil temperature and water conditions under plastic mulching were optimal to increase V. unijuga seed provisioning (mass) for high germination success in harsh subalpine environments.…”
Section: Discussionmentioning
confidence: 99%
“…H igh seed set and seed quality are highly desirable characteristics when new crop and forage species are being evaluated (Tokumoto and Nakagawa, 2015; Zohaib et al, 2018), but they are vulnerable to environmental stresses such as low or high temperatures and drought, which can prevent seed maturation or decrease offspring performance (Kong et al, 2015; Li et al, 2017; Tokumoto and Nakagawa, 2015; Walter et al, 2016). The number of seeds per pod (SP) is one of the most variable seed yield components, and it has been well documented that SP is influenced by decreasing ovule fertilization, embryo development, and final seed set under stressful conditions (Pushpavalli et al, 2015; Vleugels et al, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation